2021
DOI: 10.1101/2021.02.27.21252596
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical presentation and in-hospital outcomes of older patients hospitalized with COVID-19 in Montreal, Canada: a retrospective review

Abstract: BackgroundOlder adults are more vulnerable to severe infection and mortality due to COVID-19. They often have atypical presentations of the disease without respiratory symptoms, which makes early diagnosis clinically challenging. We aimed to compare the baseline characteristics, presentation, and disease course of older and younger patients hospitalized with COVID-19.MethodsThe charts of 429 consecutive patients hospitalized in Montreal, Canada, with PCR-confirmed COVID-19 were retrospectively reviewed. Baseli… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…A community study reported that about 40% (n = 122) have had atypical presentation of COVID-19 (fall-36%, reduced mobility-36%, and delirium-22%). In hospital admission, many older adults had no respiratory syndromes (52%) [14], but they were more likely to present geriatric syndromes, such as delirium [8,[14][15][16], functional decline [14], and falls [8,14]. A retrospective study in three medical departments in Denmark with patients ≥80 years old reported that atypical COVID-19 symptoms related to geriatric frailty syndromes were frequent, namely, confusion (29%), walking difficulty (13%), and falls (8%) [8].…”
Section: Introductionmentioning
confidence: 99%
“…A community study reported that about 40% (n = 122) have had atypical presentation of COVID-19 (fall-36%, reduced mobility-36%, and delirium-22%). In hospital admission, many older adults had no respiratory syndromes (52%) [14], but they were more likely to present geriatric syndromes, such as delirium [8,[14][15][16], functional decline [14], and falls [8,14]. A retrospective study in three medical departments in Denmark with patients ≥80 years old reported that atypical COVID-19 symptoms related to geriatric frailty syndromes were frequent, namely, confusion (29%), walking difficulty (13%), and falls (8%) [8].…”
Section: Introductionmentioning
confidence: 99%